РАЗНООБРАЗИЕ ГИСТЕРИД (COLEOPTERA HISTERIDAE) РОДА SAPRINUS КОСТАНАЙСКОЙ ОБЛАСТИ - Брагина, Т.М.; Симонова, Р.А. (My University, 2019)
Аннотация В данной статье приводятся сведения о разнообразии гистерид (Coleoptera: Histeridae) рода Saprinus (Erichson, 1834) в Костанайской области, который является самым много- численным и представлен 18 видами. Аbstract This article provides data on the diversity of hysterides (Coleoptera: Histeridae) genius Sa- prinus (Erichson, 1834 in the Kostanay region, which is the most numerous and consists of 18 species.
Diversity of hister beetles of the genus saprinus (coleoptera histeridae) from Kostanay region
Keywords: жуки гистериды (Histeridae); род Saprinus; фауна; разнообразие; Костанайская область; beetles (Histeridae); genus Saprinus; fauna; diversity; Kostanay region